2021
DOI: 10.1007/s11483-021-09696-6
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamon Essential Oil Encapsulated into a Fish Gelatin-Bacterial Cellulose Nanocrystals Complex and Active Films Thereof

Abstract: In this study, cinnamon essential oil (CEO) nanocapsules were stabilized by means of bacterial cellulose nanocrystals (BCNCs) and encapsulated using fish gelatin as the main polymer phase. Emulsions were prepared at pH 5 using different CEO concentrations (0.03, 0.06, 0.12, 0.24, 0.36, and 0.48% v/w) and a fixed amount of fish gelatin (3% w/w) and BCNCs (0.06% w/w). The controlled release of the essential oil was assessed by release studies, which revealed that the higher the CEO concentration, the lower the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 53 publications
5
12
1
Order By: Relevance
“…As expected, the respiration rate increased for all the treatments after 20 days of storage, indicating that ripening continued after harvesting due to physiological processes. A different scenario was observed after In full agreement with our previous findings [26], the protective effect against water losses was eventually emphasized at the highest applied concentration of essential oil, owing to the larger presence of hydrophobic CEO droplets which might have consistently inhibited evaporative phenomena. These results are consistent with previously reported studies in which biopolymer coatings were deposited on apples [4,16,19,21,22,24] while being in contrast with the results achieved by Sapper et al [14,15], who reported on the coating ineffectiveness to prevent or reduce weight loss from apples.…”
Section: Respiration Rate and C2h4 Productionsupporting
confidence: 86%
See 2 more Smart Citations
“…As expected, the respiration rate increased for all the treatments after 20 days of storage, indicating that ripening continued after harvesting due to physiological processes. A different scenario was observed after In full agreement with our previous findings [26], the protective effect against water losses was eventually emphasized at the highest applied concentration of essential oil, owing to the larger presence of hydrophobic CEO droplets which might have consistently inhibited evaporative phenomena. These results are consistent with previously reported studies in which biopolymer coatings were deposited on apples [4,16,19,21,22,24] while being in contrast with the results achieved by Sapper et al [14,15], who reported on the coating ineffectiveness to prevent or reduce weight loss from apples.…”
Section: Respiration Rate and C2h4 Productionsupporting
confidence: 86%
“…All the chemicals and reagents used in this study for the BCNCs-GelA/CEO nanoemulsion preparation were the same as those reported in our previous works [25,26]. The generation of BC and nanocrystals thereof was performed according to the static fermentation protocol and the sulfuric acid hydrolysis, respectively [35].…”
Section: Raw Materials and Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect tended to gradually decrease, as demonstrated by the occurrence of significant ( p < 0.05) decreases in the AI values as a function of time, especially when mild EO treatments were delivered. To this end, it must be inferred that both EO concentration and time had a significant effect up to 150 µL/L for CEO and ZEO, and up to 300 µL/L for SEO, which is linked to the release kinetics of EOs over time, as deeply discussed in our previous work [ 25 ].…”
Section: Resultsmentioning
confidence: 81%
“…Nanoencapsulation has been widely recognized as an effective technique to address the above issues, as well as to improve the solubility of EOs in water and mask their unfavorable flavor. In addition, nanoencapsulation represents a valid strategy to achieve a controlled release over time of the encapsulated active compounds via degradation and erosion of the outer polymer shell, while maintaining the physical stability of EOs [ 11 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%